Can thiol compounds be used as biomarkers of aquatic ecosystem contamination by cadmium? - Kovářová, Jana; Svobodová, Zdeňka (Interdisciplinary toxicology, 2009)
Due to anthropogenic activities, heavy metals still represent a threat for various trophic levels. If aquatic animals are exposed to heavy metals we can obviously observe considerable toxicity. It is well known that an organism affected by cadmium (Cd) synthesize low molecular mass thiol compounds rich in cysteine (Cys), such as metallothioneins (MT) and glutathione (GSH/GSSG). The aim of this study was to summarize the effect of Cd on level of thiol compounds in aquatic organisms, and evaluate that the concentrations of thiol compounds are effective indicators of Cd water pollution and explain their potential use in biomonitoring applications.
Keywords: glutathione; metal pollution; Cd; fish; metallothionein